Penentuan Desa Wisata Terbaik di Kabupaten Tabanan dengan Model AHP dan BORDA - Sugiartawan, Putu; Prakoso, Paholo Iman; Aryawan, I Made Gitra (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Tabanan Regency, is promoting the development of tourist villages and the development of many tourist villages in the area. The development of tourism villages can generate large regional income or income derived from the tourism sector. The problem is that not all tourist villages develop and generate revenue for the government, even many tourist villages are quiet from tourist visits. The selection of the best tourism village aims to find out what supporting factors can increase tourist visits and provide assistance to the tourist village. The purpose of the aid providers is to improve the quality of tourism in the area. The model used in the selection of tourist villages is the AHP and BORDA models. Both models are able to rank tourist villages from several criteria owned by tourist villages. The decision holder in this system is the Tourism Office of Tabanan Regency and the Province of Bali.